Applying Multivalent Biomolecular Interactions for Biosensors. Issue 72 (30th October 2018) - Choi, Hyeongjoo; Jung, Yongwon
Abstract: Multivalent interactions between more than one interconnected biomolecule are easily found in diverse natural systems. With the cooperation of many interacting pairs, this clustered binding can achieve highly enhanced affinities. Whereas the binding of an individual pair remains reversible, the binding between multivalent biomolecules can become nearly irreversible. Although the underlying principles of the multivalent effect have yet to be revealed, this intriguing concept of multivalent interaction has been widely applied to diverse fields. Multivalency has become a key strategy to increase the potency of inhibitors against target pathogens and, more recently, enhanced target binding by multivalency has offered an attractive strategy for biosensing. In this article, the current status of multivalent interaction studies and their progress in the biosensing area will be discussed. Abstract : Enhance your senses ! Multivalent interactions provide greatly increased binding affinities, which can be applied for biosensors with enhanced sensitivity. Recent studies also suggested that sensing selectivity may also be improved by using multivalent interactions between targets and capturing probes (see figure).